Protective Role of Osmolytes and Antioxidants during High Temperature Stress in Wheat - Satbhai, R. D.; Kale, A. A.; Naik, R. M. (International Journal of Bio-resource and Stress Management, 2015)
Ten wheat genotypes differing thermo tolerance were exposed to gradual increase of high temperature stress from control (25 °C) to 30 °C1 h, 35 °C 1 h, 40 °C 2 h and 46 °C 3 h in order to investigate its effect on RWC, chlorophyll, osmolytes accumulation, lipid peroxidation and activity of antioxidants SOD, CAT, GPOX, APX and GR. After exposed to heat stress an increment in proline and GB content was noticed in thermo-tolerant wheat genotypes and at 40 °C 2 h and 46 °C 3 h stress treatment the levels dropped in thermo-susceptible genotypes. RWC, chlorophyll ‘b’ content significantly declined with steady increase in lipid peroxidation. Heat stress induces the activity of all five ROS scavenging enzymes. However, heat inactivation of all five antioxidants observed at 46 °C 3 h stress in all wheat cultivars. Wheat genotypes NIAW-34, AKAW-4627 and NIAW-917 found to be stable. Heat stress increases GB content with higher activity of all five antioxidants could probably ameliorate the adverse effect.